The Roles of English in the Development of Tourism and Economy in Indonesia - Ida Ayu Made Sri Widiastuti; I Nengah Dasi Astawa; Ida Bagus Nyoman Mantra; Putu Herny Susanti (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
Tourism is very necessary to continue to be developed to improve the economy in Indonesia and increase the position of the country geographically, which is very strategic for tourism and the world economy. For this reason, the ability to communicate in English is absolutely necessary, in order to compete with workers from other countries, so that they can contribute to the improvement of the national economy. The ability to communicate in English is a strategic sector in the development of highly competitive human resources in the tourism industry sector and in the global economic community. By having good English communication skills, it will be easier to grab market share in the tourism industry sector and the economic sector. The tourism sector as one of the prime industrial development is developed in order to further increase the rate of national development. For this reason, it is necessary that the government continues to increase its resilience, policies, and increase the development of tourism with a view to further developing the community's economy and increasing the ability to speak English so that human resources are able to compete in various tourism industries so that the economy will increase.